If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 3(x + -6) = x + 30 Reorder the terms: 10x + 3(-6 + x) = x + 30 10x + (-6 * 3 + x * 3) = x + 30 10x + (-18 + 3x) = x + 30 Reorder the terms: -18 + 10x + 3x = x + 30 Combine like terms: 10x + 3x = 13x -18 + 13x = x + 30 Reorder the terms: -18 + 13x = 30 + x Solving -18 + 13x = 30 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -18 + 13x + -1x = 30 + x + -1x Combine like terms: 13x + -1x = 12x -18 + 12x = 30 + x + -1x Combine like terms: x + -1x = 0 -18 + 12x = 30 + 0 -18 + 12x = 30 Add '18' to each side of the equation. -18 + 18 + 12x = 30 + 18 Combine like terms: -18 + 18 = 0 0 + 12x = 30 + 18 12x = 30 + 18 Combine like terms: 30 + 18 = 48 12x = 48 Divide each side by '12'. x = 4 Simplifying x = 4
| 5x(2x-1)=35 | | 24=3(n-3) | | 11y-4=40 | | -3-3n=-n+3 | | ln(x+-3)+ln(x+2)=ln(x+-7) | | 1/5x+5h-1/5x | | -4m-13=5-m | | 6k+2=16+4k | | x+2=-68 | | 26=2x-14 | | (9i+11i)/10i | | Y-x=4x^2-8 | | -3-8x+7x=-3+5x | | 14=8z+6 | | log(7)16807=y | | 12m-71=25 | | 8p+4p+6=3p+7p | | 2x-x-3=5 | | 5b(b+4c)= | | x^2+0x+14=0 | | 247=-v+5(6v+3) | | 4y-9=27 | | 6(-1-6x)=246 | | 21/3=m/42 | | -343=-8(7-7a) | | 5(x-1)=5(4x-3) | | s^13t^8/s^2t | | 0=24x^2+28x-24 | | 3n+1=4n-2 | | -5(1-5x)+5x(-8x-2)=-4x-8x | | 24/15=20 | | 36=(6x+1)/(x-6) |